Zaključne operacije jugoslovanske 4. armade ter osvoboditev Slovenskega primorja in Trsta - Torkar, Blaž (Studia Historica Slovenica, 2016)
This paper deals with military operations and combat path of the Yugoslav 4th Army, which was established on 2 March 1945. As part of the Yugoslav Army it was involved in the final operations for the liberation of Yugoslavia. It comprised the Southern Group, which was given the task to advance in the direction Gospic-Otocac-Senj-Rijeka-Trieste towards the Isonzo River and Carinthia. The additional task was, in cooperation with the northern group of the Yugoslav liberation forces, which consisted of the 1st and 3rd Army, to surround the bulk of the enemy forces in the area Triest-Klagenfurt-Maribor-Zagreb and force them to surrender, which would facilitate the progress of the Anglo-American troops advancing from Italy and the penetration of the Red Army through Austria. The 4th Army liberated the north-western part of Yugoslavia (Lika, Croatian Littoral, Gorski Kotar, Istria, Slovene Littoral, Trieste, part of Carniola and Carinthia up to Klagenfurt). The author limited his study to the liberation of Slovene Littoral and Trieste. Special emphasis is given to the role of the IX Corps, which was a subordinate of the 4th Army during the final operations for the liberation of Yugoslavia.
Keywords: druga svetovna vojna; Jugoslavija; jugoslovanska vojska; NOB; Slovensko primorje; svetovna vojna 1939-1945; Trst